Aspectos históricos e morfofisiológicos do cafeeiro (Coffea arabica L.) em sistema agroflorestal no brejo paraibano - Carvalho, Hugo Maciel de (2023)
Coffee has always been of great importance throughout the world since it was first domesticated. It has been the subject of trade disputes among important countries and has been responsible for the economic consolidation of many nations at different times in the world history. The aim of this study was to analyse historical aspects of coffee cultivation from the domestication of the crop and its trajectory throughout the world, Brazil and the ‘Brejo Paraibano’, combining this information with the current socio-economic and environmental scenario of the ‘Brejo Paraibano’, in order to understand the potential of the coffee in the development of this region. The research was carried out in a qualitative and exploratory way using bibliographical and documentary surveys, electronic questionnaires and interviews with farmers and researchers. Coffee fruits were discovered in Absinia. During the 17th century, coffee multiplied in Europe and later in America, in the European colonies of Dutch Guiana and French Guiana, until it arrived in Brazil. Coffee adapted well in Pará, migrating to other regions, first in Maranhão, then to Ceará, Bahia and other states, adapting best in Rio de Janeiro, São Paulo, the south of Espírito Santo and the ‘Zona da Mata’ of Minas Gerais. Brejo Paraibano was an important coffeeproducing region, standing out on the national scene with approximately thirteen million coffee trees during the 19th and early 20th centuries. The current scenario is favorable to the resurgence of coffee growing in the Brejo Paraibano, as there has been a redistribution of land where local farmers have gained access and opted to develop ecologically-based cultivation and management systems that favor production and enable the sustainable development of coffee cultivation. Thus, there is a need to organize and train the families involved in production, ensure technical training, test more coffee varieties in order to indicate, multiply and distribute the most adapted and acclimatized varieties to farmers.